Evaluation of Cellular Responses for the Diagnosis of Allergic Bronchopulmonary Mycosis: A Preliminary Study in Cystic Fibrosis Patients - Michel, Moïse; Gomez, Carine; Sereme, Youssouf; Gouitaa, Marion; Chartier, Céline; Blanchard, Patricia; Pinchemel, Simon; Cassagne, Carole; Ranque, Stéphane; Mège, Jean-Louis; Reynaud-Gaubert, Martine; Vitte, Joana (Frontiers in Immunology, 2020)
Allergic bronchopulmonary mycosis (ABPM) is an underestimated allergic disease due to fungi. Most reported cases are caused by Aspergillus fumigatus (Af) and are referred to as allergic bronchopulmonary aspergillosis (ABPA). The main risk factor of ABPA is a history of lung disease, such as cystic fibrosis, asthma, or chronic obstructive pulmonary disease. The main diagnostic criteria for ABPA rely on the evaluation of humoral IgE and IgG responses to Af extracts, although these cannot discriminate Af-sensitization and ABPA. Moreover, fungi other than Af have been incriminated. Previous studies have shown the presence of fungi-specific T-cells during invasive and allergic mycosis, and flow cytometric evaluation of functional responses of basophils and lymphocytes in the context of allergic diseases is gaining momentum. Indeed, ex vivo basophil activation is a recent diagnostic tool highlighting an immediate hypersensitivity mechanism against an allergen, e.g. through a CD63 upregulation as an indirect measure of degranulation. Lymphocyte stimulation test relies on the upregulation of activation markers, such as CD69, after incubation with allergen(s), to explain a delayed hypersensitivity, for example drug hypersensitivity reactions. We hypothesized that the detection of functional responses through basophil and lymphocyte activation tests might be useful for ABPM diagnosis. We present here the results of a pilot study comparing the performance of these cellular assays versus usual diagnostic criteria. Thresholds values and associated diagnostic indices in clinical laboratories are discussed in the context of existing literature. We conclude that basophil and lymphocyte activation tests would enhance the diagnosis of allergic mycosis, compared to usual humoral markers.